A biomonitoring study: Using the biomarkers in Cyprinus carpio for the evaluation of_x000D_ water pollution in Sapanca lake (Sakarya, Turkey) - KAYHAN, FİGEN ESİN (My University, 2021)
This study aims to determine the toxic effects of heavy metal pollution on carp (Cyprinus carpio) in Sapanca Lake bybiochemical and histological analyses. For this reason, fish and water samples were taken from the lake in 2015. Heavymetal (Cu, Fe, Zn, Pb, Cd) analyzes in the water column and tissues (muscle, liver, gill) were determined by ICP-OES.CAT, GSH and MDA levels, which are oxidative stress bioindicators in tissues, were measured by spectrophotometricmethods. Histopathological findings in tissues were determined by Hematoxylin-Eosin staining. As a result, heavymetal concentrations in water were determined as Fe > Zn > Pb > Cu > Cd. The accumulation of Cu, Fe and Cd in thetissues of the fish were liver > gill > muscle, and the accumulation of Zn was gill > liver > muscle. CAT activity, MDAand GSH level of the tissues changed with the water temperature. General signs of destruction were observed in the gilltissues of the fish. Necrotic conditions in hepatocytes were observed. In conclusion, the presence of biochemical andhistopathological findings in tissues suggests that the lake is not only affected by heavy metals but also by other pollutants.